A New Figure of Merit for Solar Charging Systems: Case Study for Monolithically Integrated Photosupercapacitors Composed of a Large‐Area Organic Solar Cell and a Carbon Double‐Layer Capacitor. Issue 10 (26th August 2022) - Delgado Andrés, Rodrigo; Berestok, Taisiia; Shchyrba, Kateryna; Fischer, Anna; Würfel, Uli
Abstract : The global trend toward automatization and miniaturization of smart devices has triggered the development of reliable off‐grid power sources with low economic and environmental impact. Such autonomy can be provided when a photovoltaic cell is integrated with an electrochemical double‐layer capacitor in one monolithic power pack. This work demonstrates a reliable and straightforward approach to monolithically integrate high‐performance organic solar cells with mesoporous nitrogen‐doped carbon nanosphere‐based supercapacitors in a single device with a three‐electrode configuration. To assess the efficiency of the device, a novel approach is presented that relies on the direct monitoring of both integrating parts during illuminated and dark phases and accounts for possible losses. The evaluation with the standard literature approach shows an outstanding performance of the integrated photosupercapacitor with a peak photoelectrochemical energy conversion efficiency of 17%. However, this type of efficiency does not properly represent the real overall efficiency of the device. Based on the newly developed efficiency calculation, a more modest overall cycle efficiency of 2% is obtained, which represents the overall performance of the integrated device in a better way. This versatile evaluation approach is applicable for all kinds of integrated multifunctional photoconversion–storage systems. Abstract : A new approach for reliable performance evaluation of integrated solar charging systems is presented. It is applied to a three‐electrode photosupercapacitor produced by integration of a high‐performance organic solar cell with a mesoporous nitrogen‐doped carbon nanosphere‐based supercapacitor in a single device. The analysis shows 2% cycle efficiency and an unprecedently high photoelectrochemical energy conversion efficiency of 17%.